Association between Role Overload and Sleep Disturbance among Dementia Caregivers: The Impact of Social Support and Social Engagement. (11th June 2020) - Liang, Jiaming; Aranda, María P.; Lloyd, Donald A.
Objective: To explore the association between role overload (RO) and sleep maintenance insomnia (SMI), and the moderation effects of social support and social engagement (SE).Methods: We report a cross-sectional study using data drawn from the 2015 National Health and Aging Trends Study and National Study of Caregiving. We used multiple regression and controlled for demographics and potential confounders.Results: Nearly 45% of caregivers reported suffering from SMI during "some" and "more" nights within the past month with one half reporting "almost" or "every" night. RO was found positively associated with the risk of SMI. Instrumental support moderated the effect of RO on SMI overall, although moderation was limited to a subsample of adult children caregivers.Discussion: The sleep quality of dementia caregivers may be affected by RO, particularly for adult children caregivers. Increasing instrumental support may be beneficial to caregiver's sleep quality.